The Design, Synthesis and Structure-Activity Relationship of Antitubercular Lassomycin Derivatives - Ngqinayo, Ntombizanele (University of the Witwatersrand, Johannesburg, 2023)
Tuberculosis (TB) is a potentially fatal infectious disease caused by Mycobacterium tuberculosis (Mtb) and is a global health risk responsible for over 1.5 million deaths worldwide annually. Tuberculosis is treated with a combinatory regimen of approved first- line drugs such as rifampicin and isoniazid as well as second-line anti-TB drugs such as fluoroquinolones, most of which use similar mechanisms to cause cell death. The formation of multidrug resistance (MDR) TB strains, biofilms, and dormant persister cells (non- replicating cells) are some factors that prolong TB treatment and hence the need for developing novel antitubercular agents with a different mode of action. Furthermore, the emergence of multidrug resistance TB poses a challenge in controlling and eradicating tuberculosis. Lassomycin is a novel antimicrobial peptide (AMP) that has garnered much interest across various research groups due to its ability to effectively target and kill Mtb, including MDR strains and latent TB, with a potency that is similar to that of rifampicin. Lassomycin is highly basic and targets the highly acidic N-terminal domain (NTD) of the caseinolytic enzyme that forms part of the caseinolytic protease crucial for Mtb cell survival. Lassomycin has an unusual mode of action that causes Mtb cell death by disrupting the highly controlled and tightly regulated proteolysis by inhibiting proteolytic activities as well as increasing unfoldase activities. Thus, lassomycin shows great potential as a candidate for drug development. This study aimed to design lassomycin derivatives with improved stability and potency; and synthesize them using shorter and cost-effective synthetic routes. Peptide modifications includes (i) replacing the macrolactam ring in the peptide sequence with a disulfide bridge via a simpler ring-formation method resulting in an enlarged cyclic ring; (ii) replacing ‘difficult’ arginine residues with less basic lysine residues; (iii) forming cationic derivatives by increasing the number of basic lysine residues to enhance selectivity for the bacterial membrane; (iv) conjugating peptide derivatives to lipophilic molecules including palmitic acid and 1-adamantane carboxylic acid to improve bacterial cell penetration and binding; (v) conjugating the peptides to silver nanoparticles for improved drug delivery and antimicrobial effect; (vi) incorporating N-methylated residues to improve peptide stability; (vii) making non-polar peptide derivatives by replacing all basic amino acids with alanine to investigate the importance of the basic residues and study structure activity relationship (SAR) (viii) synthesizing linear derivatives in order to investigate the effect of the ring and (ix) shortening the peptide sequences to include only the cyclic ring or the tail sequence portions in order to shorten the synthetic route. Peptides were synthesized via the Fluorenylmethyloxycarbonyl (Fmoc) solid phase peptide synthesis strategy (SPPS) and purified using a semi-preparative High-Performance Liquid Chromatogram (prep-HPLC). They were then analysed using High-Performance Liquid Chromatography Mass Spectrometry (HPLC-MS), Circular Dichroism (CD), and nuclear magnetic resonance (NMR) spectroscopy. Silver nanoparticles and the peptide conjugates were characterized using ultraviolet-visible (UV-Vis) spectrophotometry and transmission electron microscopy (TEM) imaging. Two-dimensional (2D) Nuclear magnetic resonance (NMR) spectroscopy, including [1H, 1H] COSY, [1H, 1H] TOCSY, [1H, 13C] HSQC, [1H, 1H] HMBC and [1H, 1H] ROESY were used to determine the structural conformation of Pep-2- NN, a lassomycin derivative that has activity against tuberculosis. Furthermore, the secondary structure of selected derivatives was examined using circular dichroism (CD) spectroscopy. Computational studies were utilized to determine the structure of the active lassomycin derivatives, Pep-2-NN and Pep-2-NNA. All the peptide derivatives were successfully synthesized, including non-polar, short-chained, and those conjugated to silver nanoparticles and lipophilic molecules. The disulfide bridge was successfully added to replace the lactam bridge of the parent lassomycin peptide by oxidising sidechain thiol groups of two cysteine residues inserted at appropriate positions in the sequences. All the peptides were purified to varying degrees of success, and their behaviour was analysed to investigate structure-activity relationships. The silver nanoparticles were successfully synthesized in-house and conjugated to Pep-2-NN. Transmission Electron Microscopy (TEM) imaging revealed that the silver nanoparticles have a spherical morphology at sizes that ranged between 7 nm and 9 nm whilst peptide conjugated nanoparticles were between 9 – 12 nm. Caseinolytic protease (ClpP1P2 or ClpP) assay studies revealed that the peptides display inhibiting and activating properties when screened against the protease, including lassomycin derivatives with shortened chains such as Ring-2-NNA-Ada, Ring-2-NN, and Tail-2-NN. The secondary structure of selected lassomycin derivatives was studied using circular dichroism (CD), revealing that the structures are comprised of anti-parallel beta- (β) sheets at slightly higher proportions followed by alpha- (α) helix and, to some extent, β-turn motif. Computational studies were conducted on selected derivatives to predict their secondary structure and revealed that the peptides form stable α-helical conformations. NMR revealed that Pep-2-NN formed a ‘knotted’ structure, where the tail sequence was threaded inside the cyclic ring with a curved loop, and certain residues in the ring acted as ‘steric plugs’ to prevent unthreading. In conclusion, the insertion of the disulfide bridge remains an effective alternative to the lactam bond found originally on lassomycin and can result in the formation of biologically active derivatives with the desired stable ‘lasso’ conformation.
A research report submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, Johannesburg, 2023
Keywords: Lassomycin; Tuberculosis; Caseinolytic enzyme; ClpC1; Caseinolytic protease; ClpP; Silver nanoparticles; UCTD; SDG-3: Good health and well-being